2016
DOI: 10.1038/srep39053
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-bacterial hybrids of BamA/Tob55 suggest variable requirements for the membrane integration of β-barrel proteins

Abstract: β-Barrel proteins are found in the outer membrane (OM) of Gram-negative bacteria, chloroplasts and mitochondria. The assembly of these proteins into the corresponding OM is facilitated by a dedicated protein complex that contains a central conserved β-barrel protein termed BamA in bacteria and Tob55/Sam50 in mitochondria. BamA and Tob55 consist of a membrane-integral C-terminal domain that forms a β-barrel pore and a soluble N-terminal portion comprised of one (in Tob55) or five (in BamA) polypeptide transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…This is consistent with recent kinetic simulations showing that when Skp foldase rates are set to be equivalent to those mediated by SurA, the experimentally observed severity of the ∆ surA phenotype is not reproduced [20] . Interestingly, a recent study in yeast demonstrated that expression of E. coli Skp in the mitochondrial intermembrane space assists the assembly of some E. coli OMPs (OmpX, PhoE) into the mitochondrial OM, but not others (OmpA) [54] , consistent with the view that chaperones and BAM components perform different roles in OMP assembly, depending on substrate [55] .…”
Section: Discussionsupporting
confidence: 55%
“…This is consistent with recent kinetic simulations showing that when Skp foldase rates are set to be equivalent to those mediated by SurA, the experimentally observed severity of the ∆ surA phenotype is not reproduced [20] . Interestingly, a recent study in yeast demonstrated that expression of E. coli Skp in the mitochondrial intermembrane space assists the assembly of some E. coli OMPs (OmpX, PhoE) into the mitochondrial OM, but not others (OmpA) [54] , consistent with the view that chaperones and BAM components perform different roles in OMP assembly, depending on substrate [55] .…”
Section: Discussionsupporting
confidence: 55%
“…The large diversity of bacterial β-barrel proteins and the involvement of multiple POTRA domains and accessory Bam proteins (5, 15, 51, 60) raise the possibility that additional precursor-specific folding pathways may complement the central mechanism of β-signal exchange and sorting via the lateral gate elucidated here. For example assembly of oligomeric β-barrels in bacteria might be stalled at the BAM complex until all subunits are assembled (65), similar to the arrest of shortened precursor constructs of monomeric β-barrels (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The hidden-Markov model based homology search identified templates in the PDB with good p- and E-values. This included structures from FhaC [PDB code: 4QL0 (51)] and TamA [PDB code: 4C00 (18)] as well as several structures from BamA [PDB codes: 4K3B and 4K3C (16); 4C4V (21); 4N75 (22) and 5EKQ (23)], which exhibit considerable variations in the interaction between the β1 and β16-strands. A Sam50 model was calculated from each template using Modeller (72).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TOM40 and SAM50 together have representatives in 97.93 % of the studied proteomes (1042 out of 1064 proteomes) and this reflects their crucial biological role in the translocation of OMPs into the MOM in all eukaryotes. This process begins with the translation of mitochondrial OMPs in cytosolic ribosomes and then follows their import into the target organelles 61,62,97 . Mitochondrial proteins reach the mitochondrial surface and then are translocated into the intermembrane space across the outer membrane via the translocase of the MOM (TOM) complex 45,98 .…”
mentioning
confidence: 99%